Dominant media frames in the language of news reports from major global news stations – a case study on North Korea - Nowacki, Lukasz (2021)
The research of this thesis was conducted in order to deepen the understanding of media framing practices in global media, with direct focus on selected news stations, namely CNN, CGTN (formerly CCTV English) and Al Jazeera. This study’s primary aim was to reveal the framing trends as well as particular similarities and divergences in the reporting on the DPRK by the three global news providers, which was seen as a groundwork for the concept formulation of general framing tendencies in the contemporary media. The outcomes of the analyses have offered important insights into global media reporting of foreign news. Employing a framing approach, this study initially used content analysis to examine selected framing devices in an effort to identify types of frames, tones and sources present. Moreover, critical discourse analysis was applied to understand the link between discursive practices and the social, cultural and ideological context. Particular articles were selected and then critically analysed to enhance the content analysis results and to provide a more comprehensive picture of the framing practices adopted by the stations. While attempting to analyse frame strength and potential dominance, a gap in methodology was identified, namely a lack of empirical method of identifying frame potency. Thus, the secondary aim of this thesis became to provide a practical and a reliable method of identifying frame strength and as a result distinguish dominant media frames when in competitive context. This study found that the news discourse was dominated by conflict and attribution of responsibility regardless of the stations’ origin, ideology or political inclinations. There have been particular divergences identified between the way the stations portrayed the Democratic People’s Republic of Korea, nevertheless, the findings suggest comparable framing trends in all the selected media. On top of that, the existence of six recurring attributes of frames has been confirmed, which have the capacity to boost the potency of frames. As a result, this study proposed an exploratory method of identifying frame strength and dominance, which contributes to enhancing the ongoing studies on framing and frame construction in competitive environment. At the same time the frames studied here enabled to formulate a frame strength correlation concept according to which, frames in competitive environment will possess additional strengthening attributes to compete with other frames better, unlike single frames which remain weaker when not exposed to other frames.